2017
DOI: 10.1007/s13205-017-0944-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure of Cucumis sativus L. by using SSR markers

Abstract: The genetic variation, marker attributes and population structure was assessed in 104 genotypes of cucumber using 23 SSR primer pairs. The total number of alleles produced was 67 with an average of 2.91 per locus. Allele frequency was in the range of 0.215 to 0.561 with mean value of 0.403, polymorphic information content ranged from 0.158 to 0.495 with the mean of 0.333, marker index ranged from 0.316 to 1.54 with an average value of 0.954 and resolving power ranged from 0.346 to 2.692 with mean of 1.392. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 45 publications
3
17
1
Order By: Relevance
“…High RP values, with positive correlations with PIC and MI, indicate high descriptive potential of diversity between cucumber genotypes. Although the RP value is less than the one reported by Payel et al [40], it is higher than the one reported by Dar et al [41], who Table 3. Oligonucleotide primer sequences and real-time PCR amplification parameters.…”
Section: Issr Analysiscontrasting
confidence: 61%
See 1 more Smart Citation
“…High RP values, with positive correlations with PIC and MI, indicate high descriptive potential of diversity between cucumber genotypes. Although the RP value is less than the one reported by Payel et al [40], it is higher than the one reported by Dar et al [41], who Table 3. Oligonucleotide primer sequences and real-time PCR amplification parameters.…”
Section: Issr Analysiscontrasting
confidence: 61%
“…This result is comparable with the results of Mohammed et al [42], who reported that genetic similarity coefficients ranged between 0.15 and 0.62 in 10 cucurbit species using 13 RAPD primers. Dar et al [41] stated that Jaccard's similarity coefficient ranged from 0.07 to 0.89 for 104 genotypes of cucumber using 23 SSR primer pairs. Considering the percent of total genetic diversity, the results may not be statistically appropriate for PCA but genetically they indicate the desirable sampling of ISSR markers of the 38 cucumber genotypes.…”
Section: Clustering and Principal Component Analysismentioning
confidence: 99%
“…Our results showed average of PIC value (0.384), was similar when compared with previous findings in Indian cucumber (0.333) (DAR et al, 2017) and Chinese cucumber (0.388) (HUA et al, 2010). A wide range of genetic distance was found among the genotypes ranging from 0.03 to 0.70 which indicated a large diversity among the genotypes selected in the present study.…”
Section: Ssr Based Genetic Diversitysupporting
confidence: 92%
“…Simple sequence repeat (SSR) or microsatellite markers occur frequently in most eukaryotic genomes and can be very informative, reliable (reproducible), codominant, multiallelic and highly polymorphic, making them well suited for detecting variation among closely relative varieties (FORMISANO et al, 2012;GARCIA et al, 2004). Genetic diversity was assessed previously by using 23 SSR primer pairs in cucumber (DAR et al, 2017). Although, the degree of genetic diversity in cucumber has been assessed with a number of DNA markers (STAUB et al, 2005;ZHUANG et al, 2008;SIKDAR et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…After early domestication in India, China, and Western Asia, cucumber was introduced to Europe and the Americas [ 7 ]. Because of climatic and cultivation conditions or dietary preference during domestication, modern cultivars have diversified into the following four major types: Huánan-type (southern China), Huábei-type (northern China), European-type, and a crossbreed of Huánan × Huábei.…”
Section: Introductionmentioning
confidence: 99%